2019
DOI: 10.11648/j.ajere.20190404.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Globalization on the Performance of Small and Medium Scale Enterprises in Nigeria

Abstract: The examined the effect of globalization on the performance of small and medium scale enterprises in Nigeria. The research design adopted for the study is ex-post facto and the population of this is all the small and medium scale enterprises in Abuja. The population of the study is 72838 and was used as the sample size. Globalization was measured by trade openness and small and medium scale enterprise performance was measured by SMEs output. The study covered a period of 32 years from 1986-2018. The statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Some of phenomena above further strengthen the results of previous research, which found that using the social media can improve the employee performance (Hang, 2020). In contrast, the research results of Murat et al (2018) found that social media has no significant relationship to employee performance. The entertainment features available on social media cause employees to misuse social media for other purposes unrelated to work while working.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Some of phenomena above further strengthen the results of previous research, which found that using the social media can improve the employee performance (Hang, 2020). In contrast, the research results of Murat et al (2018) found that social media has no significant relationship to employee performance. The entertainment features available on social media cause employees to misuse social media for other purposes unrelated to work while working.…”
Section: Introductionsupporting
confidence: 78%
“…Another fact shows that each faculty has not provided clear regulations regarding the use of social media, so it is possible the employees still access other features without having anything to do with work. According to Murat et al (2018), social media has entertainment features that are feared to be misused during working hours. Therefore, it is important for organizations to regularly monitor employees so that they do not interfere with work.…”
Section: Social Media and Employee Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The caveat, however, is that this positive impact is insignificant. This implies that although SMEs benefitted from the external economies provided by trade liberalisation (as earlier endorsed by Murat and Isaac, 2019 ), the proportion of their performance associated with liberalisation is quite low or inconsiderable. Our finding is corroborated by Oladimeji and Muhammed (2017) , who document that trade openness insignificantly impacts the growth of SMEs in Nigeria.…”
Section: Data Analysis and Discussionmentioning
confidence: 92%
“…Graph 5 illustrates the trend of oil rents and PGEB in Nigeria. The country reduced its reliance on oil sector for PGEB formulation, as its trade sector and information and communications technology (ICT) domain began progressing (Murat & Isaac, 2019). In 2005, the oil rent was 18.58% of the GDP and the PGEB was 8.62%, but the tax revenue was only 2.88%.…”
Section: Graph 4: Effect Of Oil Rents On Primary Government Expenditu...mentioning
confidence: 99%